Use of pinto peanut (Arachis pintoi Krapov & WC Greg) meal in guinea pig feeding (Cavia porcellus L) - Sotelo M., Alejandrina (2018)
The aim of the present study was to evaluate the effect of pinto peanut Arachis pintoi in guinea pigs in the growing stage. The experiment lasted for 49 days and included 64 weaned male guinea pigs, arranged in a completely randomized block design with four treatments (0, 5, 10, 15% levels of A. pintoi meal), with four repetitions and four guinea pigs per repetition The results indicate that there was no significant difference between A. pintoi levels for body weight gain, feed intake, feed conversion, carcass yield and economic retribution.